Numerical analysis and animal study of noninvasive handheld electroporation delivery device for skin superficial lesion treatment - Xuyao Gao; Yuchi Zhang; Xuan Han; Zhuoqun Li; Bowen Chen; Qingshan Li; Liangshuo Hu; Yi Lv; Fenggang Ren (International Journal of Hyperthermia)
Introduction This study aims to investigate the feasibility of a noninvasive handheld electroporation pulses delivery device (EPDD) for electroporation-based treatment (EBT) of skin superficial lesions through numerical analysis and animal study.Methods Finite element analysis was performed to investigate the performance of the EPDD. The electric field, temperature, EI and TI were calculated under pulse voltages of 600, 800, and 1000 V. A mouse subcutaneous tumor model was established to evaluate the performance of the EPDD through histopathology and survival analyses.Results The electrical field strength increased from 151 (600 V) to 252 V/cm (1000 V) in the skin and from 1302 (600 V) to 2171 V/cm (1000 V) in the tumor. The volume of EI grew and reached a plateau at the 165th pulse, whereas the maximum volume of EI increased with higher voltage. The growth tendency of TI differed between groups, and it was higher in the high-voltage group (HVG) than in the low-voltage group. Histopathological analysis showed that the depth and range of the ablation area could be controlled by adjusting pulse voltage. Survival analysis showed that the survival of the HVG was better than that of the low-voltage and the control group (p < 0.01).Conclusions The results demonstrate that the EPDD is feasible, safe, and effective for skin EBT. The volume of EP tissue injury can be controlled by adjusting the pulse voltage, pulse number, and other parameters. The proposed noninvasive handheld EPDD can be a potential therapeutic tool for EBT of superficial skin lesions in the future.